PENGARUH TEPUNG DAUN INDIGOFERA (Indigofera zollingeriana) SEBAGAI SUBTITUSI BAHAN BAKU PAKAN MANDIRI TERHADAP LAJU PERTUMBUHAN BENIH IKAN GURAME (Osphronemus gouramy) - Achmad Nur Shulikin; Syahrizal Syahrizal; Safratilofa Safratilofa (Universitas Batangahari Jambi, 2021)
The high price of feed raw materials, especially protein sources, causes high commercial feed prices. One effort that can be done to reduce feed costs is to make independent feed by utilizing local forage-based raw materials such as Indigofera leaf flour (I. zollingeriana). The nutritional value of Indigofera leaf flour consists of 28.59% crude protein; crude fiber 8.96%, fat 4.12%, ash 9.33% and water content 9.25%. The purpose of this activity was to determine the effect of indigofera leaf meal (I. zollingeriana) as a substitute for independent feed ingredients on the growth rate of carp (O. gouramy) fry. The combination of treatments in a completely randomized design included: A (Without Indigofera); B (Indigofera Flour Substitutes for Fish Meal and Soybean Meal, 20% each); C (Indigofera Flour Substitute Soybean Meal 40%); D (Indigofera Flour 40% Fish Meal Substitute). Parameters observed for 60 days with sampling intervals every 10 days are Growth Rate, Feed Efficiency and Fish Survival. Data analysis used analysis of variance (ANOVA), if the results were significantly different, further tests were carried out using Duncan's test or DMRT. The use of Indigofera leaf flour by 40%, as a substitute for 20% fish meal and 20% soybean meal in treatment B, gave the best growth effect between treatments, with a growth rate of 4.78%, with feed efficiency 39.54% and sustainability. Live 92.22%. The growth rate of treatment B was not significantly different from treatment A (4.59 %), but very significantly different from treatment C (3.55%) and D (3.79 %). Independent feeds with various formulations of feed ingredients, such as fish meal, soybean meal and indigofera flour, are better because they are thought to contain more complex nutrients. Survival between treatments was not significantly different, where the F-count was smaller than the F-table or (P<0.01 or P<0.05). This means that indigofera leaves can be used as a substitute for fish meal or soybean meal and do not contain certain toxins.